O'Reilly Book Club. (O'Reilly Media, Inc., 2023)
Join us for this edition of O'Reilly Book Club with Joe Reis and Matt Housley, authors of Fundamentals of Data Engineering, to discover the stages of the data engineering lifecycle and learn to identify the various underlying components of the field, including security, data management, and orchestration. Hear from authors, learn tricks of the trade, and listen to stories. What you'll learn and how you can apply it Receive a concise overview of the data engineering landscape Learn how to evaluate the best technologies available through the framework of the data engineering lifecycle Understand data governance and security across the data engineering lifecycle This live event is for you because... You want to go beyond the words on the page and ask your own questions. You're a data engineer who wants to learn about the latest developments in the field. You're a current software engineer or data scientist who wants to transition into data engineering, or who may be doing some data engineering work in your current role. You're a data team manager who wants to understand how to better optimize your team and contribute positively to your organization. Recommended follow-up: Read Fundamentals of Data Engineering (book) Follow Data Engineering Resource Center (expert playlist).